Genetic profile of western mediterranean population : Contribution of Arab and Jewish groups - Bentayebi, Kaoutar (Université Mohammed V - Agdal, Faculté des Sciences, Rabat, 2012)
This research describes the genetic diversity of current Western Mediterranean populations through two polymorphisms: nineAlu polymorphisms and twelve Short Tandem Repeats (STR), located in the X chromosome. In this work, original results are presented forpopulations from Morocco, Spain, South of Italy and Jewish Diaspora. Our multidisciplinary study is based on biological, archaeological, historical, geographical and linguistic data in order to track the roots of the Western Mediterranean origins andgenetic history. For all markers, our results show that the North Africanare genetically close to European populations but differentiated from sub-Saharangroups. Furthermore, we notice that in North-West Africa, there isn’t any striking genetic differentiation between Berber and Arabic.The analysis of five Jewish populations plotted them in the same cluster, arguing for their shared ancestral origins that they conserved over time despite their scattering, with a clear distinction found betweenthem and their non-Jewish neighbors
Keywords: Biologie; Génétique; Western Mediterranean; Population Genetics; Forensic Genetics; North Africa; Genetic polymorphisms; STR; Alu